ผลการคัดกรองภาวะเบาหวานขึ้นจอประสาทตาของโรงพยาบาลกระทุ่มแบน จังหวัดสมุทรสาคร - Boontantrapiwat, Sinsucha; Chuen-im, Supatra (วารสารแพทย์เขต 4-5, 2018)
Objective: To evaluate incidence of diabetic retinopathy and risk factors for severe diabetic retinopathy in Krathumban Hospital, Samut Sakhon Province. Method: A cross-sectional descriptive study was performed during 1st January 2011 to 31st December 2011. The 2,219 diabetic patients of Krathumban Hospital were taken photographs from non-mydriatic fundus camera and diagnosed by the ophthalmologist. Result: Of 3,959 diabetic patients, 2,219 patients (56%) were taken into the retinal photographs. Of 2,219 photographic patients, 154 patients (6.94%) were diabetic retinopathy in a certain degree. Diabetic macular edema was detected in 11 patients (7.1%). The severity of diabetic retinopathy was scientific significantly correlated with uncontrol fasting blood sugar and hypertensive diabetic statistics.